EFEKTIFITAS STRATEGI MASTERY LEARNING DALAM PEMBELAJARAN KETERAMPILAN MEMASAK SAYUR BAGI TUNANETRA (Quasi Eksperimen di PSBN Tuah Sakato Padang) - RINA MARSALINA (Universitas Negeri Padang, 2015)
AbstractThis research was initiated by the problem found at Panti Sosial Bina Netra Tuah Sakato Padang showing that a student visual impairment was unable to saute water spinach well. She had less understanding on the steps of cooking vegetable appropriately so that she needed help to. This was a quasi experimental research which used one group pretest-posttest design. In this research, the pretest was administered to the subject prior to the treatment of Mastery Learning strategy. After the treatment given, a posttest then was conducted. The scores gotten in the pretest and posttest were analyzed and compared by using Mann Whitney U-Test. The results of the research indicated that the skill of the student with visual impairment to saute the water spinach in the pretest was 40,2% and in the posttest was 85,32%. Furthermore, the result of U-test showed that the value of Ucalculated was 0.5 and Utable was 0 in which n=4 on the significance level 95% and α = 0.05. As the value of Ucalculated was higher than Utable, it was proved that the use of Mastery Learning strategy was effective to increase the skill of the student with visual impairment to saute the water spinach. Based on this result, it was suggested to the teachers to apply Mastering Learning strategy to teach the students with visual impairment to cook.Keywords: mastery learning strategy, blind, skills, cooking, vegetable